Sunken Voices: Adivasis, Neo-Gandhian Environmentalism and State—Civil Society Relations in the Narmada Valley 1998-2001 - Whitehead, Judy (Anthropologica, 2022)
Large dams on the Narmada River have submerged some of the territories of adivasis (aboriginal peoples) of Gujarat state. Neo-Gandhian environmental movements that petitioned the Indian Supreme Court to halt dam construction recently lost their case. This paper shows that neo-Gandhian environmentalism collapsed in Gujarat for four major reasons, both external and internal. The external reasons emerge from the changing nature of state and civil society relations in the post liberalization period, in which non-governmental movements become fragments of the apparatus of consensus. The internal reasons relate to the nature of neo-Gandhian discourse, and involve the romanticization of adivasi communities and technology fetishism.